ANTISOCIAL ACTIVITIES AND ROLE OF A RELIGION IN A SOCIETY: A DESCRIPTIVE RESEARCH - Dr Mumtaz Ahmed Jasvi; Zahida Rasheed; Dr Abbas Ali Raza; Dr Hafiz Faiz Rasool, (PAKISTAN ISLAMICUS (An International Journal of Islamic & Social Sciences), 2024)
Both positive and negative activities are found in a single society. Pro society activities are beneficial and productive for a society and antisocial activities prove disaster for a society. There are multiple reasons that people get involved in antisocial activities. From many ways antisocial activities can be minimized. Many institutions play key role to make people social and fruitful for others. Family, school, media, government and religion are some social schools that play role in public socialization. A religion always play positive role in a society. It creates bond among people of different regions and castes. Some people misuse the religious activities and do antisocial activities. There are multiple reasons for this attitude. Personal benefit is one of reason. This paper is to highlight the role of a religion in combating antisocial activities in a society. The basic research question is how a religion plays its role in a society for people’s socialization. Descriptive research method will be used for this study.